Poręczne obrazy, wymowne przedmioty. Retoryka rzeczowości w „L’Esprit Nouveau” Ozenfanta i Le Corbusiera - Rejniak-Majewska, Agnieszka (Artium Quaestiones, 2019)
The paper is an attempt to draw the reader’s attention to visual reproduction as an element of modern artistic discourses and a medium of the mediated reception of art. An instrumental approach to reproduction as a neutral and ancillary vehicle of meaning, prevalent in the age of modernism, corresponded to the belief in its information efficacy and ability to overcome material, physical limitations. What mattered most were not the material, physical aspects of the existence and circulation of images, even though the avant-garde artists of the 1920s, using contemporary technology, were aware how important the medium’s and its distribution range’s “impact” was. L’Esprit Nouveau, a periodical edited in 1920-1925 by Amédée Ozenfant and Le Corbusier, was an example of a successful avant-garde strategy which let both editors, marginal in the field of art, achieve the status of “leaders” of the modernist movement, recognized or at least carefully watched by artists and critics abroad. Next to other factors, important was the visual aspect of the magazine, praised for many impressive, modern illustrations, often reproduced in other avant-garde publications. The author analyzes visual resources used and reproduced in L’Esprit Nouveau, referring to the postulates of “objectivism” and “thingness”, endorsed by the periodical, and considering the part that “ready-made” images, found in the daily press and commercial catalogues as well as on postcards. played in Le Corbusier’s polemical and programmatic texts. Their strongly persuasive message was often rooted in montage and quotations which stressed its heterogeneity. In terms of composition and aesthetics, the reproduced images supported the aesthetics of transparency, order, and thingness, so characteristic of L’Esprit Nouveau. The emblems of modernity emerged from the movement of anonymous images which acquired the value of symbols. Ozenfant’s and Le Corbusier’s use of images borrowed from popular culture, as well as from albums and art books, makes one consider not only their rhetorical effectiveness, but also their role in the creative process and thinking. In Le Corbusier’s artistic practice, those easily available, miniaturized images were a common instrument enhancing his visual, aesthetic approach. Such an approach, according to Georg Simmel, seems to be characteristic of the modernist attitude to the material world that consisted in subjective distance combined with the apparently opposite desire to “go back to things” by making them more concrete and closer to the senses.